2015
DOI: 10.1007/s10548-015-0467-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity and Quantitative EEG in Women with Alcohol Use Disorders: A Resting-State Study

Abstract: This study was aimed at exploring the electroencephalographic features associated with alcohol use disorders (AUD) during a resting-state condition, by using quantitative EEG and Functional Connectivity analyses. In addition, we explored whether EEG functional connectivity is associated with trait impulsivity. Absolute and relative powers and Synchronization Likelihood (SL) as a measure of functional connectivity were analyzed in 15 AUD women and fifteen controls matched in age, gender and education. Correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 85 publications
3
28
1
Order By: Relevance
“…These findings add support to the view that alcoholism can be considered as a disinhibitory disorder [109][110][111]. Although previous studies have separately shown that AUD was associated with altered rs-fMRI FC [3,161], poor neuropsychological performance [64,150], and heightened impulsivity [65,120], no previous FC studies have examined all three domains together as done in the current study. However, similar to the current study, we also conducted an rs-fMRI FC study, and identified distinct features from all three domains that are involved in the classification of AUD from CTL subjects [54].…”
Section: Associations Among Aud Fc Impulsivity and Neurocognitionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings add support to the view that alcoholism can be considered as a disinhibitory disorder [109][110][111]. Although previous studies have separately shown that AUD was associated with altered rs-fMRI FC [3,161], poor neuropsychological performance [64,150], and heightened impulsivity [65,120], no previous FC studies have examined all three domains together as done in the current study. However, similar to the current study, we also conducted an rs-fMRI FC study, and identified distinct features from all three domains that are involved in the classification of AUD from CTL subjects [54].…”
Section: Associations Among Aud Fc Impulsivity and Neurocognitionsupporting
confidence: 86%
“…Importantly, impulsivity was found to be associated with reduced P3 amplitude in AUD [120] and other externalizing disorders [157][158][159]. Further, recent studies have found an association of impulsivity with resting state measures of EEG power [160], EEG-based FC [161], and fMRI-based FC [3], suggesting that impulsivity in AUD may underlie specific brain networks.…”
Section: Heightened Impulsivity In Audmentioning
confidence: 91%
“…Alcohol‐associated impairments in functional connectivity were found in a recent resting‐state EEG study on women with alcohol use disorder (Herrera‐Diaz et al ). In another EEG study, acute alcohol use increased large‐scale connectivity in the resting‐state network, which was suggested to be linked to increased GABA transmission (Lithari et al ).…”
Section: Discussionmentioning
confidence: 91%
“…To date, SL has most commonly been used to characterize multiple synchronized neural sources in the brain (Stam and van Dijk, 2002) using low-density (Smit et al, 2012; Herrera-Díaz et al, 2016) or high-density EEG (Polanía et al, 2011). The major methodological advantage of using SL is that it can sensibly detect slight and intricate variations in the coupling strength (Koenis et al, 2013), resolving rapid synchronization patterns in the non-stationary ERP profile at a short time scale (Stam and van Dijk, 2002; Betzel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%